PROFIT KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGALI PERTAMA - Soemanto Soemanto (Badan Litbang dan Diklat Kementerian Agama RI, 2006)
There are three important factors influencing the success of education, namely the variables or components of : (1) hardware, software, and (3) brainware. Hardware component includes learning room for learnÂing, practicing tools, laboratory, and library. Then, software component occupies learning system, teaching program, and school management. Brain-ware, furthermore, consists of teachers, principal, students, and those are involved in teaching and learning process. Of those factors, the most important and decisive is teachers. This research-article is aimed at presenting the portrait or profile of Islamic Educational Teacher's competence in Junior Secondary School (Sekolah Menengah. Pertama) with a focus on professional competence, individual compeÂtence, and teacher's social competence.